Fucose ameliorates the proinflammatory property of Fusobacterium nucleatum in colitis via altering its metabolism - Duan, Caihan; Hou, Lingzhi; Deng, Xiaohua; Wu, Junhao; Qian, Wei; Han, Chaoqun; Hou, Xiaohua (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Previous studies reported that fucose plays a protective role in inhibiting pathogens. Fusobacterium nucleatum (Fn) was recently found to promote the progression of colitis. However, the effects of fucose on Fn are poorly understood. This study aimed to explore whether fucose could ameliorate the proinflammatory property of Fn in colitis and the underlying mechanisms. Methods To validate our hypothesis, mice were administrated with Fn and fucose-treated Fn (Fnf) before dextran sulfate sodium (DSS) treatment to establish Fn related colitis model. The metabolism variation of Fn was detected by metabolomic analysis. To verify the effects of bacterial metabolites on intestinal epithelial cells (IECs), Caco-2 cells were treated with bacterial supernatant. Results More severe inflammation, intestinal barrier damage, autophagy block, and apoptosis in the colon were noted in DSS mice that were administrated with Fn or Fnf. However, the severity degree in Fnf+DSS group was less compared to Fn+DSS group. Metabolic pathways of Fn were altered after fucose treatment and proinflammatory metabolites were decreased. The supernatant of Fnf induced a lower level of inflammation than Fn in Caco-2 cells. One of the decreased metabolites, homocysteine thiolactone (HT), was proven to induce inflammatory effects in Caco-2 cells. Discussion In conclusion, fucose ameliorates the proinflammatory property of Fn via altering its metabolism and these findings provide evidence for the application of fucose as functional food or prebiotic in the treatment of Fn related colitis.